The Syntesis of Co-Al Based Metal Oxides From Different Aluminum Sources and Their Effect on The Structural Properties - Coskuner Filiz, Bilge (GAZI UNIV, 2019)
In this research study, cobalt (Co) and aluminum (Al)-based metal oxides were produced in the spinel structure by impregnation technique by using different Al sources. The samples were synthesized by wet impregnation of cobalt (II) chloride (CoCl2 center dot 6H(2)O) on two different Al sources as boehmit (Al(OH)(3)) and corundum (alpha-Al2O3), Thermal analyses (DTA/TG) of the samples were used for understanding the effect on oxide temperature was determined. As a result of the thermogravimetric analysis, the samples were subjected to heat treatment at three different temperatures and the changes in crystal, surface and morphological structure were investigated. As a result of the structural analysis, it has been found that the Al source and the heat treatment temperature have a significant effect on the production of Co-Al oxide. As a result of experimental studies, it is suggested that boehmit (Al(OH)(3)) is used as Al source for CoAlO4 production in monophasic spinel structure and heat treatment temperature 500 degrees C is chosen after impregnation method.
Keywords: Cobalt; aluminum; metal oxide; synthesis; COAL2O4; KINETICS; Engineering